How effective is local beneficiation policy in enhancing rural income and employment? The case of agro-processing beneficiation in Tzaneen, South Africa. (June 2019) - Habiyaremye, Alexis; Mupela, Evans
Confronted with a sluggish growth and very high rates of rural unemployment, South Africa has put local beneficiation at the core of its strategy for employment-intensive re-industrialisation. Its industrial policy action plan identified agro-processing as one of the priority areas for this strategy because of its potential employment multiplier in rural areas. Despite the appeal of its industrialisation potential, beneficiation strategy is often contested and its effectiveness as a viable engine of industrialisation in African countries is recurrently questioned. This paper presents an empirical evaluation of the income and employment effects of an agro-processing beneficiation programme launched by the Department of Science and Technology for the processing of abundant mango harvest in the area of Tzaneen in Limpopo province. Using inverse probability weighting estimation on a sample of 385 households residing in and around the beneficiation target area, we find clear positive income effects of the agro-processing project for the beneficiary households. The success of this project in the domestic and international agro-processing markets suggests that local beneficiation strategy can provide a sound basis for rural industrialisation if adequately prepared.